Hook Pins in the Grave Inventories of the Wielbark Culture. A Case Study Based on the Finds from Cemeteries in Czarnówko, Lubowidz and Wilkowo Nowowiejskie, Lębork District (PL)k culture: A case study based on the finds from cemeteries in Czarnówko, Lubowidz and Wilkowo, Lębork district (PL) - Przymorska-Sztuczka, Magdalena (Analecta Archaeologica Ressoviensia, 2024)
This paper presents a special category of textile-related artefacts, hook pins, interpreted as the remains of spindles. The study is based on tools discovered in burials of the population of the Wielbark culture in Czarnówko, Lubowidz and Wilkowo Nowowiejskie, Lębork district (PL). The collected materials were not only analysed typologically but were also examined for functionality and the presence of traces of use. They were also juxtaposed with artefacts discovered at other archaeological sites from the Roman Period, including those from the area of the Przeworsk culture.